2006
DOI: 10.1093/dnares/dsi012
|View full text |Cite
|
Sign up to set email alerts
|

Complete set of ORF clones of Escherichia coli ASKA library (A Complete Set of E. coli K-12 ORF Archive): Unique Resources for Biological Research

Abstract: Based on the genomic sequence data of Escherichia coli K-12 strain, we have constructed a complete set of cloned individual genes encoding Histidine-tagged proteins with or without GFP fused for functional genomic analysis. Each clone encodes a protein of predicted ORF attached by Histidines and seven spacer amino acids at the N-terminal end, and five spacer amino acids and GFP at the C-terminal end. SfiI restriction sites are generated at both the N- and C-terminal boundaries of ORF upon cloning, which enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
1,302
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,285 publications
(1,330 citation statements)
references
References 42 publications
21
1,302
0
7
Order By: Relevance
“…16 In this case, further sequencing confirmed that the ancestral ASKA 'clone' was in fact a heterogeneous mixture of the purF (I198V) and purF(R196H) mutants; that is, these mutations did not arise in the course of our selection experiment. Nonetheless, we constructed the corrected pCA24N-purF plasmid and showed that it enabled growth on minimal selection medium at the same rate as pCA24N-purF (I198V).…”
Section: Identification Of a Promiscuous Isomerasementioning
confidence: 59%
See 2 more Smart Citations
“…16 In this case, further sequencing confirmed that the ancestral ASKA 'clone' was in fact a heterogeneous mixture of the purF (I198V) and purF(R196H) mutants; that is, these mutations did not arise in the course of our selection experiment. Nonetheless, we constructed the corrected pCA24N-purF plasmid and showed that it enabled growth on minimal selection medium at the same rate as pCA24N-purF (I198V).…”
Section: Identification Of a Promiscuous Isomerasementioning
confidence: 59%
“…DNA sequencing showed that each of these 10 clones contained the ASKA purF expression plasmid, encoding glutamine 5-phosphoribosyl-1-pyrophosphate (PRPP) amidotransferase (EC 2.4.2.14) fused to an Nterminal (His) 6 tag and a C-terminal green fluorescent protein (GFP) tag. 16 This homotetrameric, two-domain enzyme (Figure 3b) normally catalyzes the first committed step of de novo purine biosynthesis, the conversion of PRPP to phosphoribosylamine (Figure 2b). Moreover, we subsequently discovered that the two observed phenotypes (6-day growth and 10-day growth) corresponded to two genotypes.…”
Section: Identification Of a Promiscuous Isomerasementioning
confidence: 99%
See 1 more Smart Citation
“…The PNPase from E. coli was cloned in the NcoI/XhoI sites of pet33b (see Table S1). Plasmid constructs (pCA24N) for expression of the N-terminal 6xHis tagged IleRS, ThrRS from E. coli (Ec-IleRS, Ec-ThrRS) were obtained from the ASKA clone collection [26] and were expressed in the E. coli strains BL21 DE3 pLysS (Stratagen) or the strain AG1 26 respectively. …”
Section: Methodsmentioning
confidence: 99%
“…This data has been generated over many years from a large number of investigator-driven studies, as well as large-scale interactome analysis of the E. coli K-12 genome. These large-scale studies include tandemaffinity purification (TAP-tagging (Collins and Choudhary, 2008)) to isolate protein complexes, followed by their identification by mass spectrometry (MS)-MS analysis (Butland et al, 2005) and pull downs of Histagged proteins from the ASKA library (Kitagawa et al, 2005), followed by matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) analysis (Arifuzzaman et al, 2006). Although these two techniques rely on similar principle, the overlap of bona fide protein complexes between these two independent datasets is rather low, making it difficult to use as a source of information for selecting protein complexes for structural studies.…”
Section: Protein Complexes Of Bacteriamentioning
confidence: 99%